1996
DOI: 10.1103/physrevc.53.3069
|View full text |Cite
|
Sign up to set email alerts
|

Transport coefficients of a hot pion gas

Abstract: General expressions for transport coefficients of a single-component gas ͑namely, thermal conductivity and shear and bulk viscosities͒ of bosons are derived from a Boltzmann-Uehling-Uhlenbeck transport equation by means of the Chapman-Enskog method to first order. These expressions are then used for the calculation of the associated transport relaxation times and applied to the pion gas produced in ultrarelativistic heavy-ion collisions. The influence of Bose enhancement factors on transport properties can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

22
115
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(138 citation statements)
references
References 9 publications
22
115
1
Order By: Relevance
“…The picture painted by massive versus massless pions is somewhat different. Figure 9 shows the results from [29] (see also [30]), which calculated the bulk viscosity from the elastic scattering of massive pions using experimentally inferred cross sections. As for the shear viscosity, the entropy density was calculated on the basis of a free gas of pions and η, ρ and ω mesons.…”
Section: Bulk Viscositymentioning
confidence: 99%
See 1 more Smart Citation
“…The picture painted by massive versus massless pions is somewhat different. Figure 9 shows the results from [29] (see also [30]), which calculated the bulk viscosity from the elastic scattering of massive pions using experimentally inferred cross sections. As for the shear viscosity, the entropy density was calculated on the basis of a free gas of pions and η, ρ and ω mesons.…”
Section: Bulk Viscositymentioning
confidence: 99%
“…(See also [30].) The twobody interactions used went beyond the chiral approximation, and included intermediate resonances such as the ρ-meson.…”
Section: Shear Viscositymentioning
confidence: 99%
“…Note that while Grad's 14-moment approximation has been widely employed in the formulation of a causal theory of relativistic dissipative hydrodynamics [4][5][6][7][8][9][10][11][12][13][14], the Chapman-Enskog method remains less explored [15][16][17][18][19]. On the other hand, the ChapmanEnskog formalism has been often used to extract various transport coefficients of hot hadronic matter [20][21][22][23][24] Although in both methods the distribution function is expanded around its equilibrium value f 0 (x, p), it has been demonstrated that the Chapman-Enskog method in the relaxation-time approximation (RTA) leads to better agreement with both microscopic Boltzmann simulations as well as exact solutions of the relativistic RTA Boltzmann equation [16][17][18][19]. This may be attributed to the fact that a fixed-order moment expansion, as required in Grad's approximation, is not necessary in the ChapmanEnskog method.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, in practice we generally use classical statistics. The lightest hadron for which this would be the most significant approximation is the pion, but even then the difference between Bose-Einstein and classical statistics have been shown to be inconsequential for the transport coefficients for zero chemical potential [57]. While some of the material here is not original, it is basic to developing the theoretical framework.…”
mentioning
confidence: 99%